Small and Medium Sized Enterprises (SMEs) Transformation in the Digital Market Era - Teguh Setiawan Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2022)
The development of increasingly dynamic technology and information and ease of access, especially in buying and selling transactions, will support the creation of the digital market era. One of the conventional business actors in Indonesia is SMEs players. The determination of a global pandemic such as Covid-19 by the WHO in early 2020 in Indonesia had a negative effect on conventional business actors in shopping centers such as traditional markets, shops, and malls. The negative effect is in the form of a decrease in the number of buyers who visit and make buying and selling transactions at the shopping center. This is due to the emergence of the Indonesian government's policy of large-scale social restrictions, especially direct contact that was imposed during the pandemic to control the spread of Covid-19. To maintain sustainability, increase the development of SMEs players, and avoid these negative effects, changes in buying and selling transactions from the conventional market era to the digital market era need to be carried out. In this article, the discussion will focus on the right transformation of SMEs to be implemented in the current digital market era.